(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2019)
The present exploratory article analyzes the structuring of the subfield that encompasses Sport and Leisure research groups that were accordingly registered in the “Diretório de Grupos de Pesquisa no Brasil” (DGP, “Brazilian Directory of Research Groups”, our translation) until the last day of 2016. We attempted to examine how these groups were founded, where they are located, which journals their productions were published and the affiliation of the leader groups in Post-Graduation programs. Proceeding from the quantitative information provided by DGP, the Lattes academic curricula database and the theoretical background built on the French sociologist Pierre Bourdieu, we attempted to analyze these elements in light of the Field Theory, so that some logical disputes, which can be found in this subarea, can be understood. We concluded that the Sport and Leisure Research Groups are closely related with the Physical Education area and are spread throughout Brazil. However, the lack of an interdependence chain between these groups jeopardize the better comprehension of how sport and leisure have been developed in Brazil.